First results of fair-weather atmospheric electricity measurements in Northeast India - Guha, A.; De, G.K.; Gurubaran, S.; De, S.S.; Jeeva, K. (My University, 2010)
During the month of March 2006, a short campaign was conducted to measure fair-weather atmospheric electricity parameters in Tripura, Northeast India (23.50◦N, 91.25◦E). The campaign was the first of its kind in this region of the globe. The main objective of the campaign was to characterize the diurnal variation of three parameters namely vertical potential gradient (E), vertical air–earth current density (Jz) and atmospheric electrical conductivity (σ) in fair-weather conditions. The diurnal variation of E and Jz over sixteen fair-weather days shows two distinct maxima around 14UT and 20UT and a minimum around 03UT. The average vertical potential gradient is found to be 108V·m−1 and air–earth current density 1.85 pA·m−2. The average bipolar atmospheric electrical conductivity at the ground level is found to be 19.6 fS·m−1. An excellent positive correlation between E and Jz is found, with a correlation coefficient of 0.96. A comparative study with Carnegie universal variation shows 70% correlation with observed variation of vertical potential gradient during the period of the campaign. The results are discussed in view of difficulty as well as possibility of getting global signatures in atmospheric electricity measurements made from tropical land stations.
Keywords: Global electric circuit; GEC; Atmospheric vertical potential gradient; Atmospheric electricity; Air–earth current density; Atmospheric electrical conductivity